Islamic Value-Based Family Education as a Process of Internalizing Ethical and Spiritual Values - Harum Sida Rahmi; Nasikhin Nasikhin; Mustopa Mustopa (Al Yazidiy Jurnal Sosial Humaniora dan Pendidikan, 2025)
This study aims to analyze family education based on Islamic values as a process of internalizing ethical and spiritual values within Muslim families. The research adopts a qualitative approach with a case study design, where data is collected through in-depth interviews with parents and children. Data validation is conducted using source triangulation to ensure the accuracy of the findings. The results reveal that the success of internalizing Islamic ethical and spiritual values within the family does not solely depend on formal religious education but also on the quality of emotional relationships, open communication, and parental role modeling. Children tend to absorb Islamic values more easily when they feel valued and involved in the value-building process. These findings challenge the assumption that verbal teachings or mere advice are sufficient to shape an Islamic character, emphasizing the importance of a more holistic approach that focuses on affection, real-life examples, and warm dialogue. This study contributes significantly to enriching the theory of family-based Islamic education by highlighting the importance of deep emotional connections in the process of value internalization.